Assessment and management of recurrent abdominal pain in the emergency department. Issue 8 (6th December 2019) - Daniels, Jo; Griffiths, Mark; Fisher, Emma
Abstract : Recurrent abdominal pain accounts for a significant proportion of attenders and high impact users in the emergency department. Due to the heterogeneity of presentation and the broad spectrum of possible causes, abdominal pain presents as a significant clinical challenge within the emergency department, particularly as distress and pain are commonly elevated. Patients in this group are routinely prescribed opiate-based interventions and repeated investigations in a 'better safe than sorry' culture which saturates the field of persistent physical symptoms. This approach is contributing to the growing problem, and fuelling a cycle of repeated attendance and failure to resolve. This article reviews the current clinical and psychophysiological understanding of recurrent abdominal pain, critiquing guidelines and approaches to diagnosis and management. We offer an alternative evidence-based biopsychosocial approach using the mnemonic 'ERROR', recommending five steps to assessment and clinical management of recurrent abdominal pain in the emergency department.